2014
DOI: 10.1590/1516-4446-2013-1189
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia, suicidal ideation, and serum lipid levels among drug-naïve outpatients with obsessive-compulsive disorder

Abstract: Objective: As obsessive-compulsive disorder (OCD) is a relatively common psychiatric disorder with a significant suicide risk, the individuation of potential biomarkers of suicidality, such as cholesterol levels, may enable recognition of at-risk subjects. Therefore, the aims of this study were to: 1) evaluate potential differences in clinical and laboratory parameters between patients with and without alexithymia and compare them with healthy controls; and 2) investigate which clinical and laboratory variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…A suicidal act may therefore be a way of expressing intolerable psychological pain 18 . Finally, a link between serum lipid levels and suicidal ideation has been hypothesized, since some studies 19 , 20 have reported that serum lipid levels might be involved in the pathogenesis of such neuropsychiatric disorders as OCD, and that these parameters have been potentially identified as biomarkers of suicidality.…”
Section: Introductionmentioning
confidence: 99%
“…A suicidal act may therefore be a way of expressing intolerable psychological pain 18 . Finally, a link between serum lipid levels and suicidal ideation has been hypothesized, since some studies 19 , 20 have reported that serum lipid levels might be involved in the pathogenesis of such neuropsychiatric disorders as OCD, and that these parameters have been potentially identified as biomarkers of suicidality.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 A growing body of research has implicated emotion recognition proneness in the etiology and maintenance of OCD. [3][4][5] However, results from these studies are inconsistent with the findings of other studies, [6][7][8] which showed that patients with OCD were not impaired in the perception of emotion.…”
Section: Introductionmentioning
confidence: 99%
“… 5 In a recent study, OCD patients with higher alexithymic traits were also found to have a dysregulated cholesterol imbalance, which in turn may be associated with suicidal regulation. 6 …”
Section: Introductionmentioning
confidence: 99%